Analysis of Liquidity, Solvency, and Working Capital Turnover: Implications for Company Profitability in the Digital Era - Fuadi, Agus; Sulistyorini Wulandari, Dian; Nurhasan, Astrya (Journal of International Multidisciplinary Research, 2024)
This study investigates the impact of liquidity, solvency, and working capital turnover on profitability among manufacturing companies in the consumer goods sector for the 2019-2022 period. The research utilized a sample of 50 companies based on financial reports from IDX. Using purposive sampling with specific criteria, the final sample included 108 companies. The data was analyzed using multiple linear regression, processed with SPSS 25, following classic assumption tests for normality, multicollinearity, autocorrelation, and heteroscedasticity. The analysis reveals that liquidity and working capital turnover do not significantly affect profitability, while solvency significantly impacts profitability. Overall, liquidity, solvency, and working capital turnover together significantly affect profitability.